Spremljanje poseka pri gospodarjenju z gozdovi - Medved, Mirko (Gozdarski vestnik, 2008)
The purpose of the study is to determine the differences between the recorded cut and the control cut, determined on the constant sample planes, after two measurements. We compared 26 forest management units, half of them with prevailingly state owned forests. The findings show that the recorded cut in the units with prevailingly state owned forests in the most cases corresponds to the calculated control cut. In the thirteen units with prevailingly privateforest the discrepancies are larger. The control cut is often considerably higher than the recorded one, in average almost 50%. The findingsare very important for the field of planning, forest management monitoring and control, national balances of wood use and for the whole production chain of the wood-based sector. A special attention should be paid to the planning and directing of the management in the prevailingly privately owned forests.
Keywords: posek; lastništvo; gozdno gospodarstvo